Developing graduates’ collaboration skill based on Islamic perspective through integrated multi-disciplinary course in the built environment - Abdullah, Fadzidah; Azmin, Aida Kesuma; Salleh, Nurul Hamiruddin (2013)
Islam encourages collaboration in all aspects of life, in which leadership and teamwork play important roles. This Islamic obligation is pursued by the Malaysian Ministry of Higher Education’s “Teaching and Learning Taxonomy;” in which leadership and teamwork are among some of the basic soft skills that must be developed throughout the students’ study duration of the Malaysian students in tertiary educational institutions. Thus, the architecture faculty takes the challenge by instigating collaborative setting in most of the courses offered. This paper aims to discuss on Islamic perspective of collaboration, with special reference to the Integrated Multi-disciplinary course. It has the objective to examine the effectiveness of the Integrated Multi-disciplinary course, in instilling collaborative capability of leadership and teamwork, among undergraduate architectural students at International Islamic University Malaysia (IIUM). This research uses quantitative method to achieve its objective. Questionnaires were distributed among all architectural students who took the course, with n=105. Two-third of the respondents either agreed or strongly agreed that the Integrated Multi-disciplinary Course has effectively developed students’ leadership and teamwork skills. Indeed, the application of the Islamic standpoint on collaborative setting of architectural education would develop better graduates to lead the ummah, particularly in the Islamic built-environment.